PERAN FRONT OFFICE DALAM MENCIPTAKAN PENGALAMAN TAMU DI HOTEL GRIYA PERSADA BANDUNGAN - Pinasthika, Karina; Widagdo, Chrisostomus Susmono (Universitas Bina Taruna Gorontalo, 2025)
This study aims to explore the strategic role of the front office in creating a positive guest experience at Griya Persada Bandungan Hotel. Using a qualitative approach, data was collected through in-depth interviews and participant observation, involving hotel guests and front office staff as key informants. The findings reveal that initial interactions between guests and front office staff significantly influence the overall guest experience. Factors such as friendliness, prompt response to requests, and the ability to handle complaints are crucial elements that determine guest satisfaction. However, challenges in maintaining service consistency were identified due to a lack of training and increased workload during peak times. Nonetheless, the emotional aspects of the service, such as proactive behavior and interpersonal warmth, play a major role in building guest loyalty. This study concludes that improving front office service quality, including better training for staff, is essential to enhance guest experiences and increase long-term satisfaction and loyalty.